One-Pot Synthesis of Pt High Index Facets Catalysts for Electrocatalytic Oxidation of Ethanol - Ruihua Guo; Na An; Yarong Huang; Lili Guan; Guofang Zhang; Guofu Zhu; Zhaogang Liu (Nanomaterials, 2022)
Direct ethanol fuel cell (DEFC) has attracted wide attention due to its wide range of fuel sources, cleanliness, and high efficiency. However, the problems of low catalytic efficiency and poor catalyst stability still exist in DEFC catalysts, which restrict its rapid development. With chloroplatinic acid (H2PtCl6·6H2O) as the precursor, Polyvinylpyrrolidone (PVP) plays the role of surfactant, stabilizer, and reducing agent in the experiment. Glycine is the surface control agent and co-reducing agent. Pt high-index facets nanocatalyst was prepared with the one-pot hydrothermal method by adjusting the amount of PVP and glycine. X-Ray Diffraction (XRD), transmission electron microscope (TEM), and scanning electron microscope (SEM) were used to characterize the micro-structure of the nanocatalyst, and the influence of PVP and glycine on the synthesis of high-index facets catalyst was studied. The electrocatalytic performance of the catalyst was tested with an electrochemical workstation, and it was found that the performance of the prepared catalyst was better than that of the commercial catalyst. When the mass ratio of PVP and Pt was 50:1 and the molar ratio of glycine and Pt was 24:1, Pt nanocatalysts with {310}, {520} and {830} high exponential facets were prepared. The electrochemical test results showed that the peak current density of ethanol oxidation was 2.194 m2/g, and the steady-state current density was 0.241 mA/cm2, which was 5.7 times higher than that of commercial catalyst. The results of this paper show that due to the defects such as steps and kinks on the surface of the high-index facets, the active sites are increased, thus showing excellent electrocatalytic performance. This study provides a theoretical basis for the development and commercial application of high index facets nanocatalysts.